(untitled) (Bangladesh Journal of Pharmacology, 2016)
In the present study, the anti-oxidant and cytotoxic effects of the different solvent extracts of Pogostemon mollis were analyzed. The phenolic, tannin and flavonoid contents were highest in the ethyl acetate extract and analogous to the antioxidant activity results. The extracts showed activities similar to the standard anti-oxidants. The extent to which the extracts protect free radical damage on DNA was evaluated and showed good genoprotective effects. Bacterial cells and fungal spores and hyphae showed visible damages due to the treatment of ethyl acetate extract. Finally, in the cytotoxic analysis, IC50 value was calculated based on the absorbance value of different concentrations. It concluded that P. mollis is a prospective candidate for the various therapeutic applications especially its ethyl acetate extract.